2022
DOI: 10.1021/acsami.1c24263
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Durable Electrocatalysis by a Molecular Catalyst with Long Alkoxyl Chains Immobilized on a Carbon Electrode for Water Oxidation

Abstract: A dinuclear Ru complex, proximal,proximal-[Ru2L­(C8Otpy)2(OH)­(OH2)]3+ (C8Otpy = 4′-octyloxy-2,2’; 6′,2″-terpyridine) (1) with long alkoxyl chains, was synthesized to be immobilized on a carbon paper (CP) electrode via hydrophobic interactions between the long alkoxyl chains and the CP surface. The 1/CP electrode demonstrated efficient electrocatalytic water oxidation with a low overpotential (ηonset) of 0.26 V (based on the onset potential for water oxidation) in an aqueous medium at pH 7.0, which is compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
(138 reference statements)
1
8
0
Order By: Relevance
“…Yagi et al , recently reported 91% Faraday efficiency of oxygen evolution with the RuCP electrode {RuCP = immobilized proximal,proximal-[Ru 2 L(C 8 Otpy) 2 (OH)(OH 2 )] 3+ on carbon paper, where C 8 Otpy = 4′-octyloxy-2,2′; 6′,2′′-terpyridine and L = 5-phenyl-2,8-di(2-pyridyl)-1,9,10-anthyridine} for the first one hour of electrolysis at 2.01 V at pH 7. 20 The Faraday efficiency with RuCP electrode over the first 3 h decreases to 45% when the applied potential was decreased by 450 mV. In our study, when the CPE using RuPFCC was repeated at 1.81 V for 48 h a TON of >7.4 × 10 3 could be achieved.…”
Section: Resultsmentioning
confidence: 44%
See 4 more Smart Citations
“…Yagi et al , recently reported 91% Faraday efficiency of oxygen evolution with the RuCP electrode {RuCP = immobilized proximal,proximal-[Ru 2 L(C 8 Otpy) 2 (OH)(OH 2 )] 3+ on carbon paper, where C 8 Otpy = 4′-octyloxy-2,2′; 6′,2′′-terpyridine and L = 5-phenyl-2,8-di(2-pyridyl)-1,9,10-anthyridine} for the first one hour of electrolysis at 2.01 V at pH 7. 20 The Faraday efficiency with RuCP electrode over the first 3 h decreases to 45% when the applied potential was decreased by 450 mV. In our study, when the CPE using RuPFCC was repeated at 1.81 V for 48 h a TON of >7.4 × 10 3 could be achieved.…”
Section: Resultsmentioning
confidence: 44%
“…S15 † octyloxy-2,2 ′ ; 6 ′ ,2 ′′ -terpyridine and L = 5-phenyl-2,8-di(2pyridyl)-1,9,10-anthyridine} for the rst one hour of electrolysis at 2.01 V at pH 7. 20 The Faraday efficiency with RuCP electrode over the rst 3 h decreases to 45% when the applied potential was decreased by 450 mV. In our study, when the CPE using RuPFCC was repeated at 1.81 V for 48 h a TON of >7.4 × This journal is © The Royal Society of Chemistry 2023 10 3 could be achieved.…”
Section: Electrochemical Response and Oxygen Evolution Experiments Us...mentioning
confidence: 50%
See 3 more Smart Citations